PENINGKATAN MOTIVASI DALAM PENDIDIKAN ANAK USIA DINI MELALUI PARENTING CLASS DI PAUD BUAH HATI BUNDA - Ery Fatmawati; Sakinah Putri S; Sri Astuti (LPPM STIKES Madani Yogyakarta, 2019)
Education for early childhood is very important, because at that time the formation of mental and character formation is started during childhood or at the age of 0-5 years before entering school at the first level in elementary school. The parenting class program is one of the programs in strengthening family and community life, especially early childhood development, parenting methods and communication patterns run by most people. The percentage of attendance at early age education program or PAUD still reaches 70%, this is why it is necessary to increase motivation for parents to invite their children for joining the program. We used the lecture method to be able to support the early education program in the class. The activity received a positive response from the participants and the teachers in PAUD, where the participants enthusiastically participated in the activity, and the parents realized how important early childhood education was and understood the stages of brain development in human. The conclusion of this activity is that it is necessary to provide added value in the process of approach to parents of toddlers to be enthusiastic in inviting their children for education activities.